THE PREVALENCE AND PATTERN OF LIVER DISEASE IN INFANTS AND CHILDREN IN HAZARA DIVISION - Burki, Mumtaz Khan; Orakzai, Shaukat Ali (Journal of Ayub Medical College Abbottabad, 2001)
Background: The pattern of the liver disease may vary in different geographical locations. These reported variations are attributable to the differences in environmental factors, eating habits, socioeconomic factors and other reasons. We studied the pattern of liver diseases in infants and children of Hazara Division of Pakistan. Methods: 200 inpatient and outpatient infants and children in Ayub Teaching Hospital were studied from June. 1998 to October, 1999. Results: The spectrum of defect in the subjects, suffering from liver diseases showed that viral hepatitis was more common (relative frequency of 60%), followed by enteric hepatitis (26%), drug induced liver injury (7.5%), biliary atresia (5.0%) and Criglar-Najjar Syndrome (1.5%). Although both sexes were affected, however, the spectrum of liver disease was more common in males. Moreover, viral hepatitis and enteric hepatitis were found in children aging 6 to 8 years, biliary atresia in 6 months to 2 years, and drug induced liver injury in 3 to 5 years old subjects.